Il quinto elemento - Alessio, Lorena (1998)
Centro de Cómputos en Japón, proyecto de <Architect 5 Partnership>
Keywords: PROYECTOS; CENTROS DE CÓMPUTOS; HORIKOSHI, HIDETSUGU; KAWAMURA, JUNICHI; MATSUOKA, TAKEO; KIDOSAKI, HIROTAKA; JAPON